2011
DOI: 10.1182/blood-2011-01-328526
|View full text |Cite
|
Sign up to set email alerts
|

DC-like cell-dependent activation of human natural killer cells by the bisphosphonate zoledronic acid is regulated by γδ T lymphocytes

Abstract: Bisphosphonates are mainly used for the inhibition of osteoclast-mediated bone resorption but also have been shown to induce ␥␦ T-cell activation. Using IL-2-primed cultures of CD56 ؉ peripheral blood mononuclear cells, we show here that zoledronic acid (zoledronate) could induce IFN-␥ production not only in ␥␦ T lymphocytes but, surprisingly, also in natural killer (NK) cells in a manner that depended on antigen-presenting cells, which share properties of inflammatory monocytes and dendritic cells (DCs; here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 48 publications
4
72
1
Order By: Relevance
“…1B demonstrate that reconstitution with GGPP abolished IL-18 release, and inhibition of caspase-1 with the specific inhibitor YVAD (37) also abrogated IL-18 secretion (Fig. 1B), which was in accordance with our previous findings (29). IL-18 is known principally for its ability to induce IFN-g production, and cytokines, such as IL-2, can cooperate with IL-18 to enhance IFN-g production in a synergistic fashion (38).…”
Section: Zoledronate Induces An Immediate Early Cytokine Responsesupporting
confidence: 81%
See 3 more Smart Citations
“…1B demonstrate that reconstitution with GGPP abolished IL-18 release, and inhibition of caspase-1 with the specific inhibitor YVAD (37) also abrogated IL-18 secretion (Fig. 1B), which was in accordance with our previous findings (29). IL-18 is known principally for its ability to induce IFN-g production, and cytokines, such as IL-2, can cooperate with IL-18 to enhance IFN-g production in a synergistic fashion (38).…”
Section: Zoledronate Induces An Immediate Early Cytokine Responsesupporting
confidence: 81%
“…1). We showed previously that GGPP deprivation can result in functional maturation and release of IL-1b and IL-18 after proteolytic cleavage of the inactive proforms by caspase-1 and that endogenous IL-18 is the main mediator during zoledronate-induced gd T cell activation (3,28,29).…”
Section: Zoledronate Induces An Immediate Early Cytokine Responsementioning
confidence: 99%
See 2 more Smart Citations
“…In addition to their direct anti-infection activities, human cd-T cells act as professional APCs and take up, process and present pathogen-related antigens from both free viral particles 29 and infected cells 57,105 to other effector immune cells. 106,107 These cd-T APCs express approximately similar levels of HLA-DR and CD80/ CD86 compared to traditional APCs 29 and induce NK cell activation, 108,109 antigen-specific ab-T-cell responses 29,107 and even antibody production. 67 Although the physiological roles of cd-T APCs still need to be illuminated by more in vivo studies, recent investigations of murine cd-T cells have confirmed the general existence of cd-T APCs.…”
Section: Direct Anti-infection Activity Mediated By Cd-t Cells Directmentioning
confidence: 99%